Pengembangan kaligrafi digital berbasis aplikasi android untuk pembelajaran khat araby - Ahmad Yasir Amrulloh; Nino Indrianto (JINoP (Jurnal Inovasi Pembelajaran), 2022)
Media is an important component in learning Arabic calligraphy and must be presented innovatively. It was found that there were digital Arabic calligraphy stickers that were difficult to read and had errors in lettering and arrangement. This situation will lead to errors of meaning and intent. This study aims to design digital Arabic calligraphy stickers and analyze them based on material experts. This study employed the ADDIE model development method which is modified into four stages, namely: analysis, design, development and implementation. The Likert scale technique was used as an analysis to collect data from 25 PBA students as respondents. The results show that digital calligraphy stickers designed through the Android application of Ana Muhtarif al-Khat, PixelLab and Wemoji. The validation results from two material experts were “very good”. This means that the development of this product is feasible and meeting the needs of PBA students in learning Arabic calligraphy, namely being creative and innovative in utilizing media in the form of Android-based applications in making works. These results imply the need to develop various animated calligraphy stickers or GIFs to maximize learning Arabic calligraphy